A Two-hump Spectrum in the Prompt Emission of GRB 240825A - Hai-Ming Zhang; Zi-Qi Wang; Cui-Yuan Dai; Yi-Yun Huang; Wen-Qiang Liang; Ruo-Yu Liu; En-Wei Liang; Xiang-Yu Wang (The Astrophysical Journal Letters)
An extra hard spectral component that extends to GeV energies, in additional to the typical sub-MeV Band component, appears in several gamma-ray bursts (GRBs) detected by the Fermi Large Area Telescope. Only in one case (i.e., GRB 090926A) is a spectral break feature at the high-energy end identified in the extra hard component, but the photon counts are not enough to distinguish between the cutoff model and the broken power-law model for the spectral break. In this work, we report the detection of an extra hard component showing the spectral break in GRB 240825A. We find that a broken power-law model fits the spectral data of the extra component better than a single power law with an exponential cutoff in the time-resolved spectrum for the second emission pulse, with a break at about 40 MeV. This spectral feature disfavors the gamma-ray opacity to pair creation as the origin of the spectral break, but points to an intrinsic peak for the extra component. The low ratio between the peak of the extra hard component and that of the Band component challenges the synchrotron self-Compton origin for the extra component. Alternative scenarios, such as the inverse Compton scattering of the photosphere emission, are discussed. In addition, we find a clear transition from the prompt emission to afterglow emission at GeV energies in GRB 240825A, manifested by a temporal steep decay and a unique spectral evolution.